The complete denture : a clinical pathway, second edition - MacEntee, Michael I. (Chicago : Quintessence Publishing Co, Inc., 2019)
This completely updated step-by-step manual provides the knowledge and skill needed for clinicians to effectively rehabilitate patients who are completely edentulous. Treatment involving complete dentures is not simply a mechanical skill: It demands an accurate diagnosis of systemic and local problems as well as a focus on prosthetic design. In this book, the author expands on these essential skills as he describes a standardized pathway based on scientific principles to mastering the art of fabricating a complete denture.
The complete denture : a clinical pathway, second edition -- Contents -- Dedication -- Preface -- Contributors -- CHAPTER 1: Seeking the Problem -- CHAPTER 2: Impressions for Study Casts -- CHAPTER 3: Making Master Casts -- CHAPTER 4: Selecting Maxillary Anterior Teeth -- CHAPTER 5: Recording the Relationship of the Jaws and Arranging the Maxillary AnteriorTeeth -- CHAPTER 6: Arranging the Mandibular Anterior Teeth and All of the Posterior Teeth -- CHAPTER 7: Clinical Evaluation of the Teeth in Wax -- CHAPTER 8: Processing Acrylic Resin -- CHAPTER 9: Adjustment and Insertion of the Dentures -- CHAPTER 10: Relining and Repairing a Complete Denture -- CHAPTER 11: Immediate Dentures -- CHAPTER 12: Implant Overdentures -- APPENDIX 1: The Complete Denture: A Step-by-Step Summary -- APPENDICES -- APPENDIX 2: What Should You Expect from a New Denture?.
Includes bibliographical references and index.
Keywords: Denture, Complete